TiO2 nanotube immobilised 5-lipoxygenase-mediated screening and isolation of anti-inflammatory active compounds from the leaves of lonicera japonica thunb - Jinhua Zhu; Danyang Zhou; Dandan Wu; Wei Liu; Xiuhua Liu (Taylor & Francis Group, 2022)
In this work, a highly effective separation approach mediated by 5-Lipoxygenase (5-LOX) was established for screening and isolation of anti-inflammatory ingredients from leaves of Lonicera japonica Thunb. (LLJT). Using 5-LOX immobilised on TiO2 nanotubes as a microreactor, the targeted screening was exploited by combining with HPLC-MS system. Four compounds confirmed as luteolin, luteoside, lonicerin, and isochlorogenic acid C and a fraction (M1) were screened out to be potent inhibitors of 5-LOX. Their anti-inflammatory activities were further investigated and confirmed by RAW 264.7 cells inflammation model and rat foot swelling model. Furthermore, M1 was prepared by MCI GEL CHP20P column chromatography, and further separated by Pre-HPLC. One new compound confirmed to be 5,7,3',4'-tetrahydroxyflavone-7-O-sambubioside was first isolated from LLJT. The results provide a new method for the effective separation of active components derived from natural products.HighlightsA 5-LOX mediated separation method was established for isolation of anti-inflammatory compounds.An anti-inflammatory ingredient was separated by MCI GEL CHP20P column chromatography.One new compound was first isolated from leaves of Lonicera japonica Thunb.5-LOX was immobilised on TiO2 nanotubes and exploited by combining with HPLC-MS system.The anti-inflammatory activity of screened components was evaluated. [Figure: see text]